ANALISIS MISKONSEPSI SISWA MATERI HUKUM NEWTON MENGGUNAKAN WAWANCARA KLINIS DI SMPN 1 KELAM PERMAI - Sila, Innosensius; Djudin, Tomo; Firdaus, Firdaus (Universitas Tanjungpura, 2024)
The research is premised on the persistence of misconceptions among students regarding Newton's Laws at SMP Negeri 1 Kelam Permai, Sintang Regency. Consequently, an analysis of several research inquiries is imperative, focusing on: 1) Profiling the various forms of misconceptions regarding Newton's Laws among students at SMP Negeri 1 Kelam Permai, Sintang Regency; and 2) Identifying the factors contributing to these misconceptions among students studying Newton's Laws at SMP Negeri 1 Kelam Permai, Sintang Regency. This study adopts a descriptive qualitative approach, employing clinical interviews and documentation as primary data collection methods. The study's findings reveal: 1) Misconceptions among students include generalizing Newton's Laws inaccurately, inadequately defining and understanding concepts related to Newton's Laws, misclassifying Newton's Laws concepts, and misconstruing key principles; and 2) Factors contributing to these misconceptions involve students incorrectly generalizing concepts related to Newton's Laws, incomplete comprehension of fundamental attributes of Newton's Laws, misinterpretation of key elements within Newton's Laws, and a lack of focus while listening to teachers' explanations. External factors include insufficient material explanation by teachers and an inadequately conducive school environment.